Factors Associated with the Incidence of Breast Cancer in Hospitalized Patients - Aritonang, Ardelina; Kusumajaya, Hendra; Maryana, Maryana (Genius Journal, 2025)
Introduction: Breast cancer is the most prevalent type of cancer in Indonesia and a leading cause of cancer-related deaths. The annual increase in cases, particularly in the Province of Bangka Belitung Islands, makes this issue important to investigate. Factors such as age, body mass index, and hormonal contraceptive use are known to play a role in the incidence of breast cancer, yet few studies have explored this locally. Objective: This study aims to determine the factors associated with the incidence of breast cancer based on age, body mass index, and hormonal contraceptive use in the inpatient ward of RSUD Dr. (H.C.) Ir. Soekarno, Bangka Belitung Islands Province, in 2024. Method: This study employed a case-control design with a total of 176 respondents, consisting of 88 cases and 88 controls, obtained from medical records. The research was conducted from April 7 to May 18, 2025, in the inpatient wards of Class 1 RRD, Class 2 RRD, Class 3 Non-Surgical RRD, and Class 3 Surgical RRD at Dr. (H.C.) Ir. Soekarno Bangka Belitung Regional Hospital. Data collection involved obtaining permission from the Institut Citra Internasional and the hospital, identifying eligible medical records of breast cancer and non-breast cancer female patients, and conducting interviews to complete missing data. Data were then verified using a checklist and analyzed using the Chi-Square and Odds Ratio tests. Result: The results showed no significant relationship between age and the incidence of  breast cancer (p = 1.000). However, there was a significant relationship between body mass index (p= 0.000; OR = 4.956) and hormonal contraceptive use (p = 0.004; OR = 2.571) with the incidence of breast cancer. Conclusion: In conclusion, excessive body mass index and hormonal contraceptive use are significantly associated with the incidence of breast cancer. This study is important  as  a  basis for  education  and  promotive-preventive  interventions  to control risk factors.